The Negative Impact of Teen Pregnancy: Scoping Review - BR. Sitanggang, Hotmauli; Gultom, Risatantry; Simamora, Debora Lestari; Rambe, Nova Linda (CV. Devitara, 2024)
Adolescent pregnancy has now become a widespread problem that occurs in various countries, both in developing and developed countries. Adolescent pregnancy can have a negative impact on the health of the teenager itself and is one of the causes of the high maternal mortality rate. This study aims to find out the literature related to the negative impact of teenage pregnancy. The review uses methods that are compliant with the PRISMA Sc-R Guidelines, the focus of the review is determined by keywords, inclusion and exclusion criteria, the search for articles uses relevant databases, and the selection process is described in the PRISMA flowchart. Of the 450 articles selected according to the inclusion and exclusion criteria, 10 articles were reviewed in this study, five themes were found, namely: Anemia in pregnancy, Premature birth and BBLR, Preeclampsia/eclampsia, Psychological disorders and neonatal maternal death. Adolescent pregnancy has a significant negative impact on maternal health and causes death for both mother and baby.